2014
DOI: 10.1890/13-1380.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of constitutive and inducible defenses against an invasive predator

Abstract: Invasive alien predators can impose strong selection on native prey populations and induce rapid evolutionary change in the invaded communities. However, studies on evolutionary responses to invasive predators are often complicated by the lack of replicate populations differing in coexistence time with the predator, which would allow the determination of how prey traits change during the invasion. The red swamp crayfish Procambarus clarkii has invaded many freshwater areas worldwide, with negative impacts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 83 publications
(138 reference statements)
1
82
0
5
Order By: Relevance
“…Red swamp lobster ( Procambarus clarkii ), the invasive species all around the world similar to the rusty crayfish ( Orconectes rusticus ) in the US [9] is a good example of Reptantia. On one side, such an invasive animal causes ecological damage to local species [10]. On the other side, the crayfish is becoming popular food in China for its palatable taste thus catalyzes the emergence of farms.…”
Section: Introductionmentioning
confidence: 99%
“…Red swamp lobster ( Procambarus clarkii ), the invasive species all around the world similar to the rusty crayfish ( Orconectes rusticus ) in the US [9] is a good example of Reptantia. On one side, such an invasive animal causes ecological damage to local species [10]. On the other side, the crayfish is becoming popular food in China for its palatable taste thus catalyzes the emergence of farms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on the question of whether and how invasive predators affect native prey species (Gerard et al 2014;Nunes et al 2014). For example, predation experiments by Błońska et al (2015) demonstrated that the Ponto-Caspian racer goby Babka gymnotrachelus preys more on the native amphipod Gammarus fossarum than invasive Dikerogammarus villosus and Pontogammarus robustoides in its invasive range in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Even when species do not immediately recognize and respond to novel predators, selective pressures from predators have resulted in the expression of anti-predator behaviors in prey with which they have coexisted for only a few generations (Thompson 1998, Yoshida et al 2003, Nunes et al 2014, Berthon 2015. For example, native blue mussels, Mytilus edulis, from habitats invaded by the Asian shore crab, Hemigrapsus sanguineus, approximately 15 years prior (7-15 generations of M. edulis prior) increased their shell thickness in response to the crab's presence whereas completely naïve mussels from other, uninvaded populations did not respond to its presence (Freeman & Byers 2006, Zagata et al 2008.…”
Section: Chapter 1: Examining Inducible Defenses To Novel Predators Amentioning
confidence: 99%
“…Anti-predator defenses can take many forms, including physically escaping from or avoiding the predator to physical and chemical defenses (Rockwood 2006). While many anti-predator defenses are permanent, constitutive defenses, other possess temporary or plastic inducible defenses (Tollrian & Harvell 1998, Nunes et al 2014.…”
Section: Introduction: Responses Of Introduced Species To Lethal Biotmentioning
confidence: 99%
See 1 more Smart Citation